Flume Experiment on Flow Transition and Water Cushion Formation by Optimal Vegetation on a Mound Behind a Coastal Dike and Its Impact on Reducing the Flow Energy - A H M Rashedunnabi; Norio Tanaka; Md Abedur Rahman (Geosciences, 2025)
Standalone tsunami defense structures have demonstrated limitations in mitigating wave energy during the 2011 Japan tsunami. In order to mitigate future tsunamis in Japan, multi-layered protective mechanisms have been suggested or implemented after the incident. These include heightening the destroyed or existing embankment with concrete or stones, protecting embankments with concrete blocks, compacting the landward soil, elevating the ground following the coastal embankment, and incorporating green belts. Despite extensive research on the mitigation effects of such multiple countermeasures, the optimal structural configuration remains uncertain. In this study, we evaluated the performance of a multiple mitigation system consisting of a landward forest (F) on an elevated mound (M) following a seaward embankment (E) under a range of supercritical flow conditions using a flume experiment. Several mound heights and lengths were selected to determine the optimum mound for installing the forest. The combination of E and F of 12 rows of trees on M with a minimum height of 1.8 cm (Case EMFR12) created the greatest water cushion depth between E and M. When M was positioned without F, the water cushion between E and M was created by raising the height of the mound rather than its length. Conversely, a mound with a minimum height and length with a forest was found to be effective in creating the largest water cushion and maximum reduction of the flow energy. The highest energy reduction was between 45 and 70% in this experiment. These findings provide useful insights for developing multiple tsunami mitigation strategies that combine artificial and natural approaches.